Design and Evaluation of User Interface Usability for Junior High School Websites in West Papua Province Using System Usability Scale - Podajow, Devid Riswandy; Inan, Dedi I.; Juita, Ratna; Sanglise, Marlinda; Subay, Natasya Yusinta (Jutisi : Jurnal Ilmiah Teknik Informatika dan Sistem Informasi, 2024)
The primary emphasis of this study lies in utilizing the System Usability Scale (SUS) method to assess the User Interface (UI) and User Experience (UX) design. The objective is to enhance the accessibility of information at SMP YPK 01 Manokwari, a school currently facing challenges due to the absence of an official website. By concentrating on designing a user-friendly UI, this research aims to facilitate users' ease in accessing information. Through the SUS method, the UI/UX design is thoroughly evaluated to ensure optimal usability. Findings from the questionnaire, which involved 33 respondents, revealed a commendable SUS score of 83.26, categorizing the tested UI/UX design as "excellent." Consequently, the prototype UI/UX design of the SMP YPK 01 Manokwari website has been effectively developed, showcasing a high level of usability.Keywords: Design; System usability scale; User interface; User experience; Website.Â AbstrakPenelitian ini difokuskan pada penggunaan metode System Usability Scale (SUS) untuk menilai desain Antarmuka Pengguna (UI) dan Pengalaman Pengguna (UX). Tujuannya adalah untuk meningkatkan aksesibilitas informasi di SMP YPK 01 Manokwari, sebuah sekolah yang saat ini menghadapi tantangan akibat ketiadaan situs web resmi. Dengan berfokus pada merancang UI yang ramah pengguna, penelitian ini bertujuan untuk memudahkan pengguna dalam mengakses informasi. Melalui metode SUS, desain UI/UX dievaluasi secara menyeluruh untuk memastikan penggunaan yang optimal. Temuan dari kuesioner, yang melibatkan 33 responden, mengungkapkan skor SUS yang memuaskan sebesar 83.26, mengkategorikan desain UI/UX yang diuji sebagai "excellent". Akibatnya, desain prototype UI/UX dari situs web SMP YPK 01 Manokwari telah berhasil dikembangkan, menunjukkan tingkat kegunaan yang tinggi.Â